ANALISIS DESKRIPTIF TENTANG HUBUNGAN KEMAMPUAN SISWA MELAKUKAN TES HARVARD TERHADAP KECEPATAN LARI JARAK 400 METER PADA SISWA PUTRA KELAS VII SMP NEGERI 1 TANJUNGSARI - Lengkana, Anggi Setia (Jurnal Olahraga, 2016)
In this study the authors sought one form of test that has a relationship with short-distance running speeds of 400 meters. One form of test that is predicted to have a relationship to 400 meters running speed is the Harvard step up test. The test aims to measure the level of efficiency of heart, lung function, and endurance of leg muscles. This is when associated with 400 meters running speed has a significant relationship, because when performing 400 meters running, the leg muscles must have endurance speed and also supported by maximum pulmonary heart work. Based on this explanation, the writer is interested in proving it through a research process that will be tried on junior high school male students. The author formulates the problem, namely how much is the relationship between the ability of students to do the Harvard test on the running speed of 400 meters. The research hypothesis was formulated that the Harvard test had a significant relationship to 400 meters running speed. To prove this hypothesis, the author uses the descriptive method of Population and the sample used as the unit of analysis is all male students of class VII of SMP Negeri 1 Tanjungsari, amounting to 143 people. Samples were taken as many as 30 students. The instrument used in the form of a Harvard step up test and 400 meters run test. Referring to the results of the data processing of the results of tests conducted in class VII of SMP Negeri 1 Tanjungsari, conclusions can be drawn as follows: (1) Harvard test has a significant relationship to the speed of running distance of 400 meters in male students of class VII of SMP Negeri 1 Tanjungsari. This is proven by testing the hypothesis by comparing the value of t arithmetic with t table, where t arithmetic> t table = 8,491> 2.763, so that the hypothesis testing shows significant results. (2) The magnitude of the correlation coefficient between the ability of Harvard tests with the results of a 400-meter run test, the correlation (r) shows the value of 0.85, so that the magnitude of the coefficient of determination (KD) is 72.25%. Thus the null hypothesis is rejected (H0) and the research hypothesis is accepted (Ha)